PENERAPAN MODEL KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR KOGNITIF IPAS SISWA - Yulfa, Maria; Suryani Sahabuddin, Erma; Yusuf, Faidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by students' low cognitive learning outcomes in IPAS (Natural and Social Sciences), a result of instruction that remained teacher-dominated and failed to optimize student engagement. The study aimed to improve students' cognitive learning outcomes in IPAS through the implementation of the Team Games Tournament (TGT) cooperative learning model supported by flashcards. This Classroom Action Research (CAR) was conducted over two cycles with 34 fourth-grade students at UPT SPF SDN Kompleks IKIP 1, Makassar City. Data were collected through observation, learning outcome tests, and documentation. The results showed an improvement in student learning outcomes: performance was in the